The Place of 57Co-Bleomycin in the Evaluation of Tumours - Frederiksen, P. B.; Rasmussen, J. W.; Flindt-Egebak, P.; Øster-jørgensen, E. (Nuklearmedizin - NuclearMedicine, 1983)
162 patients were investigated by 57Co-bleomycin scintigraphy. 62 of these patients were also studied with 67Ga. 142 were suspected for malignant neoplastic disease, 20 for a focal inflammatory process. Good visualization with 57Co-bleomycin was obtained in 75% of malignant tumours and in 66% with 67Ga. Most of the patients were studied for abdominal disease and in this region 57Co-bleomycin was found to be qualitatively superior to 67Ga. The principal advantage of 57Co-bleomycin is a very low tissue background specially concerning the bowel. Neither 57Co-bleomycin nor 67Ga are tumour-specific. Both radiopharmaceuticals are taken up by inflammatory processes. This is a disadvantage in tumour diagnostics but the radionuclides can be useful for localizing inflammatory foci. The possibilities of studying the localisation of radionuclides at the cellular level will be discussed.